1994
DOI: 10.1192/apt.1.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing psychotropic drugs for the elderly

Abstract: The pharmacological treatment of the elderly differs from that of younger patients, mainly because of altered pharmacokinetics and the higher proportion of patients with organic disorders. We deal here with dementia, delirium, affective disorder, late-life schizophrenia, sleep disturbance, and rapid tranquillisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…As such, care home residents in Thailand, as well as internationally, are in need of effective interventions that alleviate psychological distress and physical pain and delay cognitive decline. Nonpharmacological treatments are advantageous, given older adults' vulnerability to the side effects of psychotropic medications (Burns & Baldwin, 1994). Furthermore, finite resources mean that inexpensive, efficient, and easyto-administer therapies are desirable.…”
mentioning
confidence: 99%
“…As such, care home residents in Thailand, as well as internationally, are in need of effective interventions that alleviate psychological distress and physical pain and delay cognitive decline. Nonpharmacological treatments are advantageous, given older adults' vulnerability to the side effects of psychotropic medications (Burns & Baldwin, 1994). Furthermore, finite resources mean that inexpensive, efficient, and easyto-administer therapies are desirable.…”
mentioning
confidence: 99%
“…Most modern authorities recommend that in these circumstances the neurolepüchaloperidol is the drug of choice, because of its relative freedom from cardiac, autonomie, and respiratory side-effects. Due to the risk of disabling extrapyramidal sideeffects and the relatively prolonged half-life in the elderly, titration up from a low starting dose is advised (Lipowski, 1989;Fairweather, 1990;Burns & Baldwin, 1994). The author's informal inquiries from Senior House Officers (SHOs) working in the Department of Health Care of the Elderly, Uni versity Hospital Nottingham, suggested that many junior doctors were unsure of what drug strategy to use in these circumstances and therefore an enquiry into current opinion among trainees seemed appropriate.…”
mentioning
confidence: 99%
“…Prescribing for elderly people requires careful thought. 4 Individual cases need to be assessed in terms of the relative risks and benefits but the potential for improving outcome with treatment is considerable.…”
mentioning
confidence: 99%